2016
DOI: 10.1002/2015pa002899
|View full text |Cite
|
Sign up to set email alerts
|

Plio‐Pleistocene glacial‐interglacial productivity changes in the eastern equatorial Pacific upwelling system

Abstract: The eastern equatorial Pacific Ocean (EEP) upwelling system supports >10% of the present-day global ocean primary production, making it an important component in Earth's atmospheric and marine carbon budget. Traditionally, it has been argued that since intensification of Northern Hemisphere glaciation (iNHG,~2.7 Ma), changes in EEP productivity have predominantly depended on trade wind strength-controlled upwelling intensity. An alternative hypothesis suggests that EEP productivity is primarily controlled by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(60 citation statements)
references
References 121 publications
(242 reference statements)
13
47
0
Order By: Relevance
“…Measurements of geochemical parameters (δ 13 C, δ 18 O, Mg/Ca) separately on sinistral-and dextral-coiling specimens from 25 the same samples have demonstrated that the reconstructed values are independent of the coiling directions (see also Jakob et al [2016]). …”
Section: Sample Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Measurements of geochemical parameters (δ 13 C, δ 18 O, Mg/Ca) separately on sinistral-and dextral-coiling specimens from 25 the same samples have demonstrated that the reconstructed values are independent of the coiling directions (see also Jakob et al [2016]). …”
Section: Sample Materialsmentioning
confidence: 99%
“…These intervals are from 2.68 to 2.65 .65 mcd corresponding to MIS G3) and from 2.73 to 2.69 .79 mcd corresponding to MIS G7-G5). We decided not to 30 fill these gaps by using another size fraction because (i) this might have biased our Mg/Ca and stable-isotope records due to ontogenetic effects (Elderfield et al, 2002;Friedrich et al, 2012), and (ii) the abundance of G. crassaformis specimens <315 For G. ruber, the previously published Mg/Ca-based SST and δ 18 O datasets of Jakob et al (2017) were augmented by δ 13 C data, except for the interval from ~2.65 to 2.4 Ma for which δ 13 C values have already been published by Jakob et al (2016). For this purpose, an average of twelve specimens was picked from the 250-315 µm size fraction.…”
Section: Sample Materialsmentioning
confidence: 99%
See 3 more Smart Citations